Studying the Properties of SBS/Rice Husk Ash-Modified Asphalt Binder and Mixture - Zhen Lu; Aimin Sha; Wentong Wang; Junfeng Gao (Advances in Materials Science and Engineering)
Sustainable materials in the field of road pavement have become a research direction in recent years. In this study, the rice husk ash with small dosage of styrene-butadiene-styrene (SBS) was added as a bioadditive into the base asphalt to modify its properties. Different contents (0, 2, 5, 10, and 15%) of rice husk ash (RHA) and 1% of SBS were selected to prepare the modified asphalt. Penetration, softening point, ductility, rotational viscosity test, and temperature sweep test were conducted to investigate the properties of SBS/RHA-modified asphalt binder. Rutting test, moisture susceptibility, and low-temperature cracking were utilized to evaluate the performances of SBS/RHA-modified asphalt mixture. The results showed that the penetration decreased and the softening point and rotational viscosity enhanced while the ductility slightly decreased with the incorporation of rice husk ash. The SBS/RHA-modified asphalt mixture had better high-temperature performance than that of the virgin asphalt mixture but slightly lower moisture stability and low temperature performance. The tensile strength ratio of the virgin and modified asphalt mixture met the requirement of specification. The tensile strain of mixture SR15 was lower than the requirement for the asphalt mixtures on the basis of the specification. For the SBS/RHA-modified asphalt binder based on the comprehensive properties, the content of rice husk ash should not be higher than 15%.